APLIKASI MIKORIZA UNTUK MENINGKATKAN PERTUMBUHAN BEBERAPA JENIS RUMPUT MAKANAN TERNAK TERHADAP CEKAMAN KEKERINGAN PADA TANAH PODSOLIK JANTHO - Elviwirda Elviwirda; Sufardi Sufardi; Syakur Syakur (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2016)
Problems that arise in forage supply are continuity of farm and it’s low productivity and limited soil water availability in dry season. This study aims to: 1) examine the role of AMF on the growth of some types of grass fodder by different levels of water stress on podzolic soil; and 2) understand the interaction between application of AMF in different water stress and the types of grass on growth of forage grasses. This research was conducted in plastic house of Field Laboratory of Assessment Institute for Agricultural Technology (BPTP) Aceh. Randomized block design (RAK) with 6 x 3 factorial for three replications was used. The first factor was application the AMF and water stress which consists of six levels, namely: C1 = Without AMF + water stress 60% of field capacity, C2 = Without AMF + water stress 80% of field capacity, C3 = Without AMF + without water stress (100 % of field capacity), C4 = AMF + water stress 60% of field capacity, C5 = AMF + water stress 80% of field capacity, C6 = AMF + without water stress (100% field capacity). The second factor was type of grass that consists of three levels, namely: R1 = Brachiaria decumbens, R2 = Brachiaria mutica, R3 = Cynodon plectostachyus. The parameters observed in this research were canopy fresh weight, root dry weight, leaf relative water content. Results showed AMF addition of water stress 60% of field capacity on Jantho podzolic soil increased the canopy fresh weight, root dry weight, and leaf relative water content. There were interaction effects between applications AMF at different water stresses and the types of grass against canopy fresh weight, root dry weight and leaf relative water content.